Dynamics of battered filipino women validating a dynamics of abuse model - Estrellado, Alicia F. (Silliman Journal, 2010)
This study was designed to validate Estrellado and Salazar-Clemeña's (2007) Dynamics of Abuse Model. It also aimed to further and analyze dynamics of Filipino battered women. A quantitative study of 20 battered women was conducted using in-depth interview. PArticipants reported 19 categories of abuse, 20 categories of contributing factors to abuse, 16 categories of effects of abuse on women's perception of self, view of the world, sense of well-being, and interpersonal relationships, and 13 categories of coping strategies. Responses were coded based on Estrellado and Salazar-Clemeña's model. The study demonstrated that Dynamics of Abuse Model can be useful as a conceptual framework for understanding concerns of battered women. Implications for counseling and research are discussed.